THE INCIDENT OF CONSTIPATION AMONG STROKE PATIENT IN THE WARD AT DR SLAMET HOSPITAL GARUT - Cecep Eli Kosasih; Tetti Solehati (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction. The incidence of complication especially constipation among stroke patients was so much. It cause discomfort during hospitalization. During the stroke patient was treated at the hospital, some patients experienced some limitations both physically and mentally. Those limitations encourage high incidence of complications of constipation, especially in patients who experience immobility in bed. The aim of the study was to identify the most dominant factor that causes constipation in stroke patients. Method.. This study used cross sectional design for data collection on constipation causative factors (diet, fluids, and exercise) and the incidence of constipation. The sample in the study was 40 samples of stroke patient who treated in Dr Slamet Hospital. Data were analyzed by using multiple logistic regressions. Result.There was a significant relationship between constipation with dietary intake with ρ value of 0.004 (α <0.05), exercise with ρ value of 0.034 (α <0.05), and fluid with ρ value of 0.019 (α <0.05). Discussion. To prevent constipation and maintain a normal defecation process in stroke patients should consume enough fluids, exercise regularly and mainly dietary fiber intake is sufficient. For nurses and other health care team should consider the needs of each dietary fiber and fluids are also trained in stroke patient exercise regularly. Keywords: Dietary factors, fluid, exercise, constipation